What Is the Optimal Follow-up Length for Mortality in Staphylococcus aureus Bacteremia? Observations From a Systematic Review of Attributable Mortality. (10th April 2022) - Bai, Anthony D; Lo, Carson K L; Komorowski, Adam S; Suresh, Mallika; Guo, Kevin; Garg, Akhil; Tandon, Pranav; Senecal, Julien; Del Corpo, Olivier; Stefanova, Isabella; Fogarty, Clare; Butler-Laporte, Guillaume; et al.
Abstract: Background: Deaths following Staphylococcus aureus bacteremia (SAB) may be related or unrelated to the infection. In SAB therapeutics research, the length of follow-up should be optimized to capture most attributable deaths and minimize nonattributable deaths. We performed a secondary analysis of a systematic review to describe attributable mortality in SAB over time. Methods: We systematically searched Medline, Embase, and Cochrane Database of Systematic Reviews from 1 January 1991 to 7 May 2021 for human observational studies of SAB. To be included in this secondary analysis, the study must have reported attributable mortality. Two reviewers extracted study data and assessed risk of bias independently. Pooling of study estimates was not performed due to heterogeneity in the definition of attributable deaths. Results: Twenty-four observational cohort studies were included. The median proportion of all-cause deaths that were attributable to SAB was 77% (interquartile range [IQR], 72%–89%) at 1 month and 62% (IQR, 58%–75%) at 3 months. At 1 year, this proportion was 57% in 1 study. In 2 studies that described the rate of increase in mortality over time, 2-week follow-up captured 68 of 79 (86%) and 48 of 57 (84%) attributable deaths that occurred by 3 months. By comparison, 1-month follow-up captured 54 of 57 (95%) and 56 of 60 (93%) attributable deaths that occurred by 3 months in 2 studies. Conclusions: The proportion of deaths that are attributable to SAB decreases as follow-up lengthens. Follow-up duration between 1 and 3 months seems optimal if evaluating processes of care that impact SAB mortality. Clinical Trials Registration: PROSPERO CRD42021253891. Abstract : In Staphylococcus aureus bacteremia (SAB), the proportion of deaths attributable to SAB decreases as follow-up lengthens. The ideal follow-up for mortality in SAB should be between 1 and 3 months.